Law Enforcement Against Environmental Damage As a Result of Direct Disposal of Waste Incompatible with Environmental Management Efforts - Andi Khuswatun Khasana (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Humans grow and develop with their environment. All human interactions, both between humans and with the environment have positive and negative impacts on the environment. Therefore, legal regulations must regulate the balance between humans and their environment. Environmental law and all its facilities and conditions with people who are in and affect the environment. Therefore, as an important subject in the process of developing the environment, we as humans must preserve and protect our environment as well as possible.